GAMBARAN SERABUT SARAF PADA TIPE PERADANGAN APENDISITIS DENGAN PULASAN IMUNOHISTOKIMIA S-100 DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PEKANBARU PERIODE JANUARI 2008-DESEMBER 2013 - VONY BESTARI; WIWIT ADE FIDIAWATI; SUINDRA " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Appendicitis is an inflammation of the appendix that is often associated with an infection that occurs in the appendix. In appendicitis inflammation there are several histological criteria in the diagnosis of acute or chronic inflammation is, one that neuronal dysplasia. Ectopic nerve fibers is one form of dysplasia neurons. The research was done by applying paraffin blocks of patients with acute appendicitis and chronic outward S100. S100-specific antibody is an antibody that is used to see the nerve fibers. The results were obtained ectopic nerve fibers more abundant in chronic appendicitis is 89.47%, while 77.27% of acute appendicitis. Based on the age that children and adults, ectopic nerve fibers as is not so significant in children 83.33% and 82.35% in adults. By sex is male (88.89%) more than in women (78.26%). This ectopic nerve fibers can cause prolonged transit time.Keywords: appendicitis, ectopic nerve fibers, S100 protein antibody